Profil Penggunaan Obat Antihipertensi di RSUD Mas Amsyar Kasongan Kabupaten Katingan: A Profile of Antihypertensive Medicines in Mas Amsyar Hospital Kasongan Katingan Regency - Syahrida Dian Ardhany; Wahyu Pandaran; Mohammad Rizki Fadhil Pratama (Borneo Journal of Pharmacy, 2018)
Hypertension or high blood pressure is one of the lead causes of death. Hypertension can cause various complications with another disease, even the cause of heart disease, stroke, and kidney disorders. Hypertension is the second rank of the most diseases in Kabupaten Katingan. The purpose of this research is to know the profile of antihypertensive medicines in RSUD Mas Amsyar Kasongan. Method of this research was a descriptive method with saturation sampling used retrospective data on all prescription drugs in 2017. The results of this research based on the patient characteristic were found 43.3% men and 56.7% women, meanwhile 45.8% age < 45 years old and 54.2% for age > 45 years old. The antihypertensive drug items used are propranolol, telmisartan, amlodipine, lisinopril, furosemide, ramipril, valsartan, candesartan, irbesartan, and bisoprolol, meanwhile based on the classification of antihypertensive drugs. are angiotensin II receptor blockers (ARB), diuretics, angiotensin converting enzyme Inhibitors (ACEI), Calcium Channel Blockers (CCB) and alpha 2 adrenergic agonists. Based on the result, it can be concluded that hypertension patient in RSUD Mas Amsyar Kasongan is mostly female (56.7%) and age of hypertension patient is > 45 years old (54.2%). The most antihypertensive prescribed is monotherapy (72%) and the most item of the drug is amlodipine. (38%).